The anthropogenic perturbation of the marine nitrogen cycle by atmospheric deposition: Nitrogen cycle feedbacks and the 15N Haber‐Bosch effect. Issue 10 (9th October 2016) - Yang, Simon; Gruber, Nicolas
Abstract: Over the last 100 years, anthropogenic emissions have led to a strong increase of atmospheric nitrogen deposition over the ocean, yet the resulting impacts and feedbacks are neither well understood nor quantified. To this end, we run a suite of simulations with the ocean component of the Community Earth System Model v1.2 forced with five scenarios of nitrogen deposition over the period from 1850 through 2100, while keeping all other forcings unchanged. Even though global oceanic net primary production increases little in response to this fertilization, the higher export and the resulting expansion of the oxygen minimum zones cause an increase in pelagic and benthic denitrification and burial by about 5%. In addition, the enhanced availability of fixed nitrogen in the surface ocean reduces global ocean N2 fixation by more than 10%. Despite the compensating effects through these negative feedbacks that eliminate by the year 2000 about 60% of the deposited nitrogen, the anthropogenic nitrogen input forced the upper ocean N budget into an imbalance of between 9 and 22 Tg N yr −1 depending on the deposition scenario. The excess nitrogen accumulates to highly detectable levels and causes in most areas a distinct negative trend in the δ 15 N of the oceanic fixed nitrogen pools—a trend we refer to as the 15 N Haber‐Bosch effect. Changes in surface nitrate utilization and the nitrogen feedbacks induce further changes in the δ 15 N of NO 3 −, making it a good but complex recorder of the overall impact of the changes in atmospheric deposition. Key Points: The anthropogenic increase in atmospheric N deposition initiates a series of strong negative feedbacks in the marine N cycle The excess N accumulates in the ocean to detectable levels The accumulation of anthropogenic N causes a negative trend in the N of oceanic fixed N pools that has the potential to dilute climate driven N signals